Clinical And Laboratory Characteristics Of Congenital Hypothyroidism In Newborn - Septi Wardani; Esteve Adrian Estiva; Marcos Ochoa; Liwayway Vallesteros; Arby James Abonalla; Arlene Mandal (Asosiasi Guru dan Dosen Seluruh Indonesia, 2026)
Congenital Hypothyroidism (CH) is the most common congenital endocrine disorder in newborns and can lead to delayed neurocognitive development if not detected and treated early. Clinical manifestations of CH in the neonatal period are often atypical, so laboratory tests play a crucial role in establishing the diagnosis. This study aims to determine the clinical and laboratory characteristics of congenital CH. Hypothyroidism in newborns. This study used a retrospective descriptive design with a cross-sectional approach. The study sample consisted of 40 newborns diagnosed with congenital hypothyroidism. Hypothyroidism was diagnosed based on screening results and thyroid hormone examinations. Data obtained from medical records included clinical characteristics and laboratory results of TSH and T4 levels. The results showed that most infants did not show specific clinical symptoms early in life. The most common clinical manifestations were prolonged jaundice, hypotonia, and low birth weight. Laboratory examinations showed increased TSH levels and decreased T4 levels in all samples. It was concluded that the diagnosis of congenital hypothyroidism was correct. Hypothyroidism in newborns relies heavily on laboratory tests because clinical symptoms are often nonspecific.